Setting Ruang Permukiman dalam Pengembangan Ruang Bermukim Di Kepulauan Togean Sulawesi Tengah - Ahda Mulyati; Nindyo Soewarno; Arya Ronald; A Sarwadi (Forum Teknik, 2011)
Togean the islands are cluster of the small islands located in the district of Tojo Una-una and the very excited tourist attraction in Central Sulawesi Province. Some of the cluster of the islands is the settled place Bajo communities who occupied the coastal areas and the small islands. The islands are formed from the volcanic activity with the fertile plants as well surrounded by the rocks formations. Piles of the rocks to forms and functions as a place to living. Togean the islands has an area of ±362,000 ha and has been designated as one of the Marine National Park in the Indonesia. Case study research approah used with multiple cases, naturalistic quantitative data collection with analysis techniques in exploration.The islands in the islands Togean as a shelter the coastal communities particularly in the settlements on the islands of Enam/Enau (district Togean) and the island Kabalutan (district Walea the island). The two these islands setting show a very specifically lived spaces because it is strongly influenced by of nature physical factors, socio-economic conditions, and the local wisdom there. The development of the settlement spaces setting formal due to : (a) the limited land areas as a dwelling allocation, (b) presense of land potential that can be developed to support the economic life and the preservation of natural environment, and (c) the environmental suistainability of its settlement that a unique and specific. Keywords : Setting Space, Housing, Development Settlement